Long-Term Problems in Children and Adolescents with Congenital Heart Disease and the Role of Pediatric Nurses in the Follow-Up - Merve Ertunç Soycan; Ayfer Aydın (CURARE Journal of Nursing)
Due to advances in care and technology, the life expectancy of children with congenital heart disease has been prolonged, which has brought long-term problems to the agenda at the same time. In the long-term follow-up of children with congenital heart disease, physical health problems such as growthdevelopmental retardation, neurodevelopmental issues, oral and dental health problems, decreased physical activity, obesity, and malnutrition, as well as psychosocial issues such as decreased social relationships, depression, anxiety, and attention deficit were observed. These problems negatively affect children’s healthy lifestyle behaviours. Children and adolescents with congenital heart disease can gain healthy lifestyle behaviours through health counselling. Therefore, this article highlights the long-term problems in children and adolescents with congenital heart disease and the role of pediatric nurses in their follow-up. This review provides practical recommendations for nursing care and highlights the need for a multidisciplinary approach to improve the quality of life.